CULTURAL TRANSFORMATION OF CHINESE LANGUAGE LEARNING IN THE AI ERA (Proceeding of SINERGY, 2026)
The integration of artificial intelligence (AI) into foreign language education has significantly reshaped learning practices, particularly in the learning of Chinese as a foreign language. Given the inseparable relationship between language and culture in Chinese language education, the increasing use of AI-based tools raises important questions regarding cultural transformation in learning processes. This study investigates how AI-assisted learning influences students’ cultural perceptions, learning habits, and engagement with Chinese cultural content. Using a quantitative descriptive approach, data were collected through an online survey involving 46 undergraduate students from the Chinese Language and Culture Program at Universitas Padjadjaran, Indonesia. The questionnaire examined students’ frequency of AI usage, perceived impact on language learning, and perceived changes in cultural awareness. The findings reveal that AI-based tools contribute not only to learning efficiency but also to shifts in how students access, interpret, and internalize Chinese cultural elements. While AI supports understanding through instant explanations and contextualization, it also encourages a more pragmatic and global-oriented view of Chinese culture. This study highlights the cultural implications of AI integration in Chinese language learning and underscores the importance of balancing technological innovation with cultural depth in higher education.